(untitled) (Scientific journal of the Fergana State University, 2026)
This article studies the chemical pollution, salinity and their ecological consequences of soils around a cement plant located in the Karauzak district of the Republic of Karakalpakstan. During the study, the impact of cement dust, heavy metals (Cr, Cu, Cd, Pb,Ni), and other pollutants on soil parameters such as pH, carbonate content, humus, nutrients (NPK), and enzyme activities (urease, catalase, invertase ) was assessed. Laboratory analyses were conducted on samples taken at different depths (0-15 cm) at 200 m, 1500 m, and 5000 m from the cement Plant. The results showed that the amount of pollutants decreased with increasing distance from the cement plant. Wind speed and direction, land use characteristics, and soil morphology affected the level of pollution. Such conditions have a negative impact on the ecological functions, biological activity and nutritional properties of the soil. Local scientific research has also noted a decrease in the level of salinity, enzyme activity (urease, catalase, invertase) and humus content in soils under the influence of cement dust. In particular, iron oxide, chromium, nitrogen oxide and carbon compounds that fall into the soil along with dust reduce biodiversity and inhibit enzyme activity. Under the influence of cement dust, alkalization of the soil pH value is observed, which has a negative impact on the absorption of nutrients in the long term.